2020
DOI: 10.1021/acs.jced.9b01051
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of d-Histidine in Aqueous Cosolvent Mixtures of N,N-Dimethylformamide, Ethanol, Dimethyl Sulfoxide, and N-Methyl-2-pyrrolidone: Determination, Preferential Solvation, and Solvent Effect

Abstract: This work mainly focused on d-histidine solubility in N,N-dimethylformamide (DMF) + water, ethanol + water, dimethyl sulfoxide (DMSO) + water, and N-methyl-2-pyrrolidone (NMP) + water mixtures. All experiments were performed at temperatures between T = 293.15 and T = 333.15 K at intervals of 5 K by a shake-flask method. The largest solubility of d-histidine was found in the neat solvents of NMP (DMF or DMSO) for the NMP (DMF or DMSO) mixtures and water for the ethanol mixture. The values of mole fraction solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
(117 reference statements)
0
7
0
Order By: Relevance
“…It has been reported that imidazole and amino acid Pro can stabilize the interaction of the lysozyme–NAG 3 complex. ,, Here, imidazole, amino acids, acetonitrile, NMP, and DMF were applied to lysozyme solutions with flavonoids for ESI-MS, respectively. Both NMP and DMF are common cosolvents used in the pharmaceutical field and show high solubilization ability. , It was found that addition of imidazole, amino acids, and acetonitrile could not improve the stability of lysozyme–flavonoid complexes (data not shown), and only DMF and NMP were found to be very good at stabilizing the labile lysozyme–flavonoid complexes.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that imidazole and amino acid Pro can stabilize the interaction of the lysozyme–NAG 3 complex. ,, Here, imidazole, amino acids, acetonitrile, NMP, and DMF were applied to lysozyme solutions with flavonoids for ESI-MS, respectively. Both NMP and DMF are common cosolvents used in the pharmaceutical field and show high solubilization ability. , It was found that addition of imidazole, amino acids, and acetonitrile could not improve the stability of lysozyme–flavonoid complexes (data not shown), and only DMF and NMP were found to be very good at stabilizing the labile lysozyme–flavonoid complexes.…”
Section: Resultsmentioning
confidence: 99%
“…The last term indicates the energy term for solvent–solvent interactions, where c i = 1–4 demonstrates the sensitivity of solute solubility to the corresponding solute–solvent and solvent–solvent molecular interactions. The independent coefficient c 0 shows the effect of the crystal lattice properties of the solute on the solubility . It is also called the ideal solubility ( x ideal ) estimated by the solid–liquid phase equilibrium thermodynamics (described by eq ).…”
Section: Model Calculation Sectionmentioning
confidence: 99%
“…The independent coefficient c 0 shows the effect of the crystal lattice properties of the solute on the solubility. 22 It is also called the ideal solubility (x ideal ) estimated by the solid−liquid phase equilibrium thermodynamics (described by eq 10). 23…”
Section: Model Calculation Sectionmentioning
confidence: 99%
“…Furthermore, some aqueous mixtures of NMP have been analyzed in cosolvency studies for increasing the equilibrium solubility of several drugs and drug-like compounds, as was compiled in the published literature. , The specific compounds include terephthalic acid, sebacic acid, , 1,12-decanedioic acid, 1-naphthoic acid, , phenobarbital, griseofulvine, , phenytoin, ,, ketoprofen, , estrone, , testosterone, , ibuprofen, ,, amiodarone, , carbendazim, , 2-phenoxypropionic acid, , (2 R )-2-[4-(7-chloroquinoxalin-2-yl)­oxyphenoxy]­propanoic acid (XK-469), , a benzoylphenyl urea derivative, , 2-(2-thiophenyl)-4-azabenzoimidazole (PG-300995), , clonazepam, diazepam, lamotrigine, acetaminophen, amiodarone·HCl, celecoxib, 6-methyl-2-thiouracil, ketoconazole, allopurinol, chloroxine, d -histidine, 5-aminosalicylic acid, bisacodyl, amoxicillin, 5-nitrofurazone, biapenem, phenformin, griseofulvine, and sulfadiazine …”
Section: Introductionmentioning
confidence: 99%